Pengaruh Kreativitas Strategi Pemasaran, Inovasi dan Orientasi Kewirausahan Terhadap Kinerja Pemasaran melalui Keunggulan Bersaing sebagai Variabel Mediasi pada UMKM Batik di Kota Yogyakarta dalam Masa Pandemik Covid-19 - Marsiana Numat; Ambar Lukitaningsih; Lusia Tria Hatmanti Hutami (LPPM Institut Nasional Laa Roiba Bogor, 2022)
Marketing performance as a benchmark to find out how far the success of Batik MSMEs in the city of Yogyakarta facing intense competition. This studi aims to determine how the influence of marketing strategy creativity, innovation and entrepreneurial orientation marketing performance through competitive advantage as a modiating variable in batik MSMEs in Yogyakarta City during the covid-19 pandemic. The type of research used in non- probability sampling with a total sample of 100 respondens using purposive sampling technique. Collecting data using a oqestionnaire with a likert measurement scale. Data were analyzed using SPSS 20.0 for windows. There is signifikan influence of marketing strategy creativity, innovation and entrepreneurial orientation on marketing performance and competitive advantage and there is a significant influence of marketing strategy creativity, innovation, and entrepreneurial orientation on marketing performance through competitive advantage. Keywords: marketing strategy creativity; innovation; entrepreneurial orientation; competitive advantage, marketing performance